DETECTION, TRANSMISSION, AND EXPRESSION cDNA GROWTH HORMONE GENE (PhGH) OF STRIPPED CATFISH IN F-1 TRANSGENIC AFRICAN CATFISH - Huria Marnis; Bambang Iswanto; Rommy Suprapto; Imron Imron; Raden Roro Sri Pudji Sinarni Dewi (Indonesian Aquaculture Journal, 2014)
In previous study, the fast growth transgenic founder of African catfish was produced harboring a growth hormone (GH) gene construct containing a stripped catfish growth hormone (PhGH) cDNA. This study was conducted to investigate transgene (PhGH) transmission and expression in F-1 transgenic African catfish. The transgenic founders (female) were crossed with non-transgenic (male) to produce heterozygous F-1 progeny. PhGH gene was detected in the embryo, larvae, and seed of the transgenic F-1 using PCR method. Expression levels of transgene in embryo and larvae were analyzed using real-time quantitative PCR (qPCR) method. The transgene was detected in embryo, larvae and seed of F-1 transgenic African catfish. Founder could transmit PhGH gene to transgenic F-1 lines in ranged 36% to 48%. Expression level of Phgh gene in embryo was higher than that of the larvae; whereas in the embryo was 1.5 x 105 - 5.2 x 105 copies or 0.49-9.82 fold, while in the larvae was 1.1 x 105 - 2.5 x 105copies or 0.19-5.80 fold.